Association of HSP22 with mTOR in osteoblasts: regulation of TNF‐α‐stimulated IL‐6 synthesis. Issue 7 (23rd March 2018) - Sakai, Go; Tokuda, Haruhiko; Yamamoto, Naohiro; Matsushima‐Nishiwaki, Rie; Fujita, Kazuhiko; Kawabata, Tetsu; Kozawa, Osamu; Otsuka, Takanobu
Abstract : Heat shock protein 22 (HSP22) is ubiquitously expressed in various types of cells including in osteoblasts. We previously reported that tumor necrosis factor (TNF)‐α stimulates interleukin (IL)‐6 synthesis via p44/p42 MAPK in osteoblast‐like MC3T3‐E1 cells and that mTOR/p70 S6 kinase (p70 S6K) negatively regulates the IL‐6 synthesis. In this study, we investigated the involvement of HSP22 in TNF‐α‐stimulated‐IL‐6 synthesis and the underlying mechanism in MC3T3‐E1 cells. HSP22 knockdown reduces TNF‐α‐stimulated release of IL‐6. In addition, HSP22 knockdown strengthens TNF‐α‐induced phosphorylation of p70 S6K but suppresses that of p44/p42 MAPK. HSP22 coimmunoprecipitates with mTOR. HSP22 knockdown increases the basal levels of phosphorylated mTOR. These results strongly suggest that HSP22 interacts with mTOR and regulates TNF‐α‐induced IL‐6 synthesis in osteoblasts. Abstract :